Cassava technology transfer in the Philippines - Gundaya, Editha A.; Evangelio, Fernando A.; Sanico, R.T.; Roa, J.R.; Orias, Ramón R.; Ramírez, M.C.U. (International Center for Tropical Agriculture, 1995)
After several years of conducting research in cassava, the Philippine Root Crop Research and Training Center (PRCRTC) developed technologies that may raise the crop's potential and help uplift the welfare of Filipino farmers, processors and consumers. To fully tap this potential, PRCRTC, in cooperation with the national agricultural extension service, conducted extension activities to transfer the technologies to the intended users, i.e. small or large-scale producers, processors, entrepreneurs and other interested individuals or groups. The technology transfer is being done through training, publications, exhibits, radio broadcasts and pilot commercialization projects. These activities gained momentum only recently, but substantial progress can already be observed. These include the people's increasing awareness of the cassava technologies, spread of the PRCRTC-recommended varieties in some parts of the country and the eight operational village-scale cassava processing projects in the Visayas and Mindanao regions. While conducting the different technology transfer activities, PRCRTC learned important lessons that led to the implementation of the Integrated Root Crop Extension Program. A case study on the establishment of a cassava processing project following an integrated approach is presented. Problems on cassava technology transfer and some suggestions for improvement are also discussed